Motivational factors were more important than perceived risk or optimism for compliance to infection control measures in the early stage of the COVID-19 pandemic. - Bjørn Sætrevik; Sebastian B Bjørkheim (PLoS ONE, 2022)
Compliance to infection control measures may be influenced both by the fear of negative consequences of a pandemic, but also by the expectation to be able to handle the pandemic's challenges. We performed a survey on a representative sample for Norway (N = 4,083) in the first weeks of the COVID-19 lock-down in March 2020. We had preregistered hypotheses to test the effect of optimism and perceived risk on compliance. Perceived risk had small effects on increasing compliance and on leading to more careful information gathering. The expected negative association between optimism and compliance was not supported, and there was instead a small positive association. We found a small effect that optimism was associated with seeing less risk from the pandemic and with a larger optimistic bias. Finally, an exploratory analysis showed that seeing the infection control measures as being effective in protecting others explained a substantial proportion of the variation in compliance. The study indicates that how we think about pandemic risk has complex and non-intuitive relationships with compliance. Our beliefs and motivations toward infection control measures appears to be important for compliance.